The impact of career expectation on employment anxiety of art students in higher vocational colleges during the COVID-19: A chain mediating role of social support and psychological capital - Zhao, An (Frontiers in Psychology, 2023)
Objective: In the process of college students’ employment, psychological capital and social support play a vital role. Methods: This study examined the relationship between career expectation and employment anxiety of Chinese vocational art college students (N = 634). Participants completed the Career Expectation Scale (CES), Employment Anxiety Scale (EAS), Psychological Capital Scale (PCS) and Social Support Scale (SSS). Results: (1) Vocational art students’ career expectation has a positive predictive effect on employment anxiety, social support and psychological capital; Social support and psychological capital have negative predictive effects on employment anxiety. (2) Social support and psychological capital play a significant chain intermediary role between career expectation and employment anxiety, and there is a masking effect. Conclusions: These results are of guiding significance to the improvement of the employment quality of art students in higher vocational colleges and the employment consulting work in colleges.